Electron microscopic studies on the location of bacterial proliferation in the liver in murine salmonellosis. - Lin, F. R. (1987)
Highly susceptible inbred male C57BL/6 mice were infected with 2 X 10(7) virulent Salmonella typhimurium by intraperitoneal inoculation. Samples of the liver were removed 2 or 3 days post-infection for examination by electron microscopy. Rapid infiltration of polymorphs and macrophages was observed in the site of infection. Visual evidence is presented to confirm the destruction of salmonellae within these inflammatory phagocytes as previously reported. The proliferation of the pathogens occurred in the extracellular locations of sinusoids and early lesions, and within hepatocytes.